Atmospheric H2S and SO2 as sulfur source for Brassica juncea and Brassica rapa: impact on the glucosinolate composition - Aghajanzadeh, Tahereh; Kopriva, Stanislav; Hawkesford, Malcolm J.; Koprivova, Anna; De Kok, Luit J. (Frontiers in Plant Science, 2015)
The impact of sulfate deprivation and atmospheric H2S and SO2 nutrition on the content and composition of glucosinolates was studied in Brassica juncea and Brasscia rapa. Both species contained a number of aliphatic and indolic glucosinolates. The total glucosinolate content was more than 5.5-fold higher in B. juncea than in B. rapa, which could solely be attributed to the presence of high levels of sinigrin, which was absent in the latter species. Sulfate deprivation resulted in a strong decrease in the content and an altered composition of the glucosinolates of both species. Despite the differences in patterns in foliarly uptake and metabolism, their exposure hardly affected the glucosinolate composition of the shoot, both at sulfate-sufficient and sulfate-deprived conditions. This indicated that the glucosinolate composition in the shoot was hardly affected by differences in sulfur source (viz. sulfate, sulfite and sulfide). Upon sulfate deprivation, where foliarly absorbed H2S and SO2 were the sole sulfur source for growth, the glucosinolate composition of roots differed from sulfate-sufficient B. juncea and B. rapa, notably the fraction of the indolic glucosinolates was lower than that observed in sulfur-sufficient roots.